ANALISIS DAMPAK TRANSFORMASI STRUKTURAL TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - Musniasih Yuniati; Rohmiati Amini; Ihsan Ihsan (Universitas Pahlawan Tuanku Tambusai, 2022)
Structural transformation causes the transformation of the workforce from sectors with relatively low incomes to sectors with relatively higher incomes. An increase in income in the long term will improve the welfare of the community. The purpose of the study was to determine the impact of structural transformation on the welfare of the people of Central Lombok Regency, West Nusa Tenggara. The research method used is descriptive qualitative. The analysis was carried out qualitatively based on quantitative data. The results of the study indicate that there has been a change in the economic structure of Central Lombok because the contribution of the agricultural sector has decreased while the contribution of the non-agricultural sector has increased. Structural transformation has an impact on people's welfare. Welfare indicators used in the analysis are BPS welfare indicators. Based on the population and employment indicators, it is indicated that there has been an increase in welfare, while the education indicator indicates that it has not yet achieved prosperity because the value of the pure participation rate is still low, mainly at the Sekolah Dasar/Menengah (SD/M) level. Poverty indicators show that the poverty rate has decreased and the rupiah value of the minimum expenditure required for a person to meet the basic needs of his life for a month, both food and non-food needs has increased. Keywords: Structural transformation, community welfare